Risk Analysis of the 150 kV Overhead Line and Cable Construction Projects of Kariangau Substation Toward GIS 4 in The Nusantara Capital - Mustakim, Lutfi; Dinariyana, A. A. B. (GoAcademica Research & Publishing, 2025)
The development of Nusantara Capital (IKN) was legalized based on Law No. 3 of 2022 on State Capital (UU IKN). One of PLN’s projects in IKN is the construction of a 150 kV overhead transmission line and cable from the Kariangau Substation (GI) to Gas Insulated Switchgear (GIS) 4 IKN. This project has challenges related to the large investment value and complexity, so a comprehensive risk analysis is needed to ensure the success of the project. This research is essential, because based on the data, based on data, 8 out of 10 PLN projects in Kalimantan completed in 2022 and 2023 have experienced a time overrun of 1 to 3 years and cost overrun 10% to > 20%. This study aims to analyze the risks of the project using a multi-method approach. Data were collected through the PLN UIP Kalbagtim 2022 Risk Assessment Report, literature reviews, interviews, and questionnaire surveys. The risk identification process identified 12 risk variables consisting of 63 risk criteria, risk analysis using the Severity Index (SI) method to determine the probability and impact values. The risk analysis results categorized the risks as follows: 2 extreme risk criteria, 30 high-risk criteria, 19 moderate-risk criteria, and 12 low-risk criteria. The Delphi method is used to determine alternative recommendations for risk responses for extreme and high-risk categories. The Analytical Network Process (ANP) method is used to identify priority risks and recommendations for risk responses to priority risk. The results of this study found three (3) priority risk variables: Land Acquisition risk with the highest weight of 0.20183, Right of Way (ROW) Clearence risk with a weight of 0.16829 and Permitting risk with a weight of 0.16564. Recomendations for priority risk responses to Land Acquisition risk includes forming a Task Force team to accelerate verification of land payment documents, involving community leaders, and provide transparent socialization regarding the appraisal process. For ROW Clearance risk, the recommendations include forming a Task Force to accelerate the verification of ROW documents, conducting consignment (depositing ROW compensation values in court), and collaborating with banks to facilitate the creation of mass accounts for ROW compensation payments. For Permitting risk, the recommendations include create a list of required permits and compile a submission timeline, holding audiences with relevant stakeholders to increase support for project activities, and conducting regular checkpoints to ensure document completeness before submitting permits.